DURABILITY OF LIGHTWEIGHT CONCRETE IN AGGRESSIVE ENVIRONMENTS (Spectrum Journal of Innovation, Reforms and Development, 2022)
A One of the important requirements for solutions and concretes based on mineral binders is their resistance to the effects of various aggressive media on them. The fact that concrete and reinforced concrete products and structures based on Portland cement binder are not always durable enough when exposed to some natural waters has been established for a long time.